UNITED KINGDOM NORMS FOR THE HARVARD GROUP SCALE OF HYPNOTIC SUSCEPTIBILITY, FORM A. Issue 1 (2nd January 2020) - Oakley, David A.; Walsh, Eamonn; Lillelokken, Ann-Mari; Halligan, Peter W.; Mehta, Mitul A.; Deeley, Quinton
ABSTRACT: The Harvard Group Scale of Hypnotic Susceptibility, Form A (HGSHS:A), is widely used as a measure of suggestibility to screen participants for research purposes. To date, there have been a number of normative studies of the HGSHS:A, the majority of which originate from Western countries. The outcomes of these Western studies are summarized, and variations in methodologies are described and discussed. Also reported are the psychometric properties of the HGSHS:A in a large contemporary United Kingdom (UK) sample. Overall, these UK results are consistent with the earlier Western norms studies in terms of response distribution and item difficulty, with only minor differences. The continued use of HGSHS:A as a screening procedure is supported, particularly if corrected for response subjectivity/involuntariness and with revised amnesia scoring. The HGSHS:A is also important as a potential measure of the broader trait of direct verbal suggestibility.